1966
DOI: 10.1017/s0003356100037673
|View full text |Cite
|
Sign up to set email alerts
|

The effects of level of feeding of sows during pregnancy. I. Reproductive performance

Abstract: 1. Twelve sets of 3 litter-sister Large White gilts were mated at first oestrus after reaching 250 lb. live-weight and given daily during 3 successive pregnancies either 6 lb. (A), 3 lb. (B) or 3 lb. for 76 days then 6 lb. until parturition (C) of the same meal mixture. During an 8-week lactation all were given 4 lb. meal plus 0·8 lb. per piglet suckled.2. There was a significant linear increase in numbers born with successive parities (P<0·05) but no significant differences between treatment or sister grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
20
0

Year Published

1970
1970
1991
1991

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 7 publications
6
20
0
Order By: Relevance
“…This result agrees with other trials in which neither the level of feeding nor the level of energy intake of the sow during pregnancy influenced pig numbers (Clawson et al 1963;Lodge et al 1966;Lodge 1969). However, for pigs born alive in Parity I it was found that sows on the higher feeding level had litters which contained significantly more pigs than their contemporaries on the lower feeding level.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This result agrees with other trials in which neither the level of feeding nor the level of energy intake of the sow during pregnancy influenced pig numbers (Clawson et al 1963;Lodge et al 1966;Lodge 1969). However, for pigs born alive in Parity I it was found that sows on the higher feeding level had litters which contained significantly more pigs than their contemporaries on the lower feeding level.…”
Section: Discussionsupporting
confidence: 92%
“…These studies showed that increases in the level of feeding of the sow during pregnancy increased average piglet birth weight (Dean and Tribble 1961;Henson et al 1964;Lodge et al 1966). Similarly, increases in average birth weights have resulted from increases in energy intake during pregnancy (Clawson et al 1963;.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The TDN values werc75.9,78.3 and 73.IVo from digestibility studies on the 30th and 9fth days of gestation and lfth day of lactation, respectively. (5,6) have considered the influence of severe energy restriction on the sow and her offspring, and the results indicate that the offspring are protected to a major degree even when sows are losing weight. IJltimately, however, sows must be able to maintain their weight throughout repeated reproductive cycles.…”
Section: Digestibilitymentioning
confidence: 99%
“…Lower piglet birth weight the pregnant sow have an effect on without any effect on litter size was found reproductive performance only at treatment when energy intake was restricted to 4688 extremes. Gossett and Sorensen (1959) vs. 9316 kcal metabolizable energy observed a larger litter size and a higher (ME)/day (Clawson et al 1963) or 2.2 vs. embryo survival rate in sows fed free choice 9.0 Mcal digestible energy (DE)/day a diet containing 1213 kcal productive (Buitrago etal.1974 (Lodge et al 1966), or 0.9 and 1 .4 vs. 1.9, 2.4 and3.0 kg (Baker et al 1969). In second parity, sows with average daily gains (ADG) of 0.02 and 0.34 kglday, there was no effect on fetal survival (Dyck 197 (Dyck 1974b (Svajgr et al 1912).…”
mentioning
confidence: 99%